2012
DOI: 10.1103/physrevlett.109.196802
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Intrinsic and Robust Nature of van Hove Singularities in Twisted Bilayer Graphene by Scanning Tunneling Microscopy and Theoretical Analysis

Abstract: Extensive scanning tunneling microscopy and spectroscopy experiments complemented by firstprinciples and parametrized tight binding calculations provide a clear answer to the existence, origin, and robustness of van Hove singularities (vHs) in twisted graphene layers. Our results are conclusive: vHs due to interlayer coupling are ubiquitously present in a broad range (from 1 to 10 ) of rotation angles in our graphene on 6H-SiC(000-1) samples. From the variation of the energy separation of the vHs with the rota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

48
331
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(382 citation statements)
references
References 51 publications
48
331
1
2
Order By: Relevance
“…These singularities were identified as the peaks appeared symmetrically with respect to the Fermi level in scanning tunneling spectra of twisted bilayers for rotation angles between 1 and 108. [86,87] The features of the lowenergy band structure can be understood by considering the Brillouin zones of superposed layers. As a result of rotation, the Dirac cones originating from individual layers separate and their intersection at a higher energy produces the two saddle points (Fig.…”
Section: Stacked Graphene Layersmentioning
confidence: 99%
“…These singularities were identified as the peaks appeared symmetrically with respect to the Fermi level in scanning tunneling spectra of twisted bilayers for rotation angles between 1 and 108. [86,87] The features of the lowenergy band structure can be understood by considering the Brillouin zones of superposed layers. As a result of rotation, the Dirac cones originating from individual layers separate and their intersection at a higher energy produces the two saddle points (Fig.…”
Section: Stacked Graphene Layersmentioning
confidence: 99%
“…A full-tight binding calculation showed a reduction of the Fermi velocity due to interlayer interaction 2 . For TG with small twist angles (yo15°), the experimental studies showed 1,3,6,9 that the Dirac cones for each layer persist but van Hove singularities are present due to the interlayer interaction. For large twist angles, the twisted layers effectively de-couple from each other and become indistinguishable from SLG 7 .…”
mentioning
confidence: 99%
“…T he rotational stacking of graphene layers alters their electronic characteristics resulting in novel and rich physics [1][2][3][4][5][6][7][8] . Bernal (AB)-stacked graphene rotated by 60°b etween adjacent layers is well understood and its electronic properties are radically different from single-layer graphene (SLG).…”
mentioning
confidence: 99%
“…The electronic properties of moiré crystals depend sensitively on the ratio of the interlayer hybridization strength, which is independent of twist angle, to the band energy shifts produced by momentum space rotation (5)(6)(7)(8)(9)(10)(11)(12). In bilayer graphene, this ratio is small when twist angles exceed about 2° (10,13), allowing moiré crystal electronic structure to be easily understood using perturbation theory (5).…”
mentioning
confidence: 99%